Potential Use of Ascophyllum nodosum as a Biostimulant for Improving the Growth Performance of Vigna aconitifolia (Jacq.) Marechal - Nidhi Verma (MDPI AG, 2021)
The fertilizers that are derived from seaweed are known as Seaweed Liquid Fertilizers (SLF). SLF is a modern, cheap, non-toxic, and natural bioactive fertilizer. Among different studied seaweeds, Ascophyllum nodosum is significant as having bioactive ingredients that potentially regulate the molecular, physiological, and biochemical processes of crop plants. In the present study, the effects of the application of different concentrations (0.00%, 0.01%, 0.02%, 0.05%, 0.10%, 0.50%, and 1.00%) of A. nodosum Extract (ANE) to the Vigna aconitifolia through roots (Pot Root Application, PRA) and on the leaves (Pot Foliar Application, PFA) were monitored via the plant growth. The lower concentrations of ANE in both the PRA and PFA experiments showed positive growth on V. aconitifolia. The 0.10% ANE stimulated the maximum shoot growth when applied through the roots, while 0.05% ANE in both PFA and PRA experiments led to an increase in the number of pods, nodules, organic content, and moisture percentage. The 0.10% ANE also increased the leaf numbers, leaf area, and photosynthetic pigments. Hence, the application of 0.05% and 0.10% of A. nodosum extract in two ways (i.e., Pot Foliar Application, PFA, and Pot Root Application, PRA) ameliorated the growth capabilities of V. aconitifolia.